Risk management concepts and guidance - Pritchard, Carl L. (Gildan, 2019)
This new edition of Risk Management: Concepts and Guidance supplies a look at risk in light of current information, yet remains grounded in the history of risk practice. Taking a holistic approach, it examines risk as a blend of environmental, programmatic, and situational concerns.
Online resource; title from title details screen (OverDrive, viewed March 1, 2019)
Keywords: Project management -- Decision making; Risk management; Gestion de projet; Prise de décision; Gestion du risque; risk management; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Downloadable audio books; Audiobooks; Livres audio